2004
DOI: 10.1023/b:joec.0000048784.79031.5e
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Volatiles That Are Used in Discrimination Between Plants Infested with Prey or Nonprey Herbivores by a Predatory Mite

Abstract: Carnivorous arthropods can use herbivore-induced plant volatiles to locate their herbivorous prey. In the field, carnivores are confronted with information from plants infested with herbivores that may differ in their suitability as prey. Discrimination by the predatory mite Phytoseiulus persimilis between volatiles from lima bean plants infested with the prey herbivore Tetranychus urticae, or plants infested with the nonprey caterpillar Spodoptera exigua, depends on spider mite density. In this article, we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
167
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(180 citation statements)
references
References 15 publications
5
167
0
4
Order By: Relevance
“…Spider mite-infested tomato plants emit signiWcantly more TMTT than uninfested tomato plants . The role of TMTT in the attraction of predatory mites has been investigated with lima bean (Phaseolus lunatus) as model system (De Boer et al 2004). Predatory mites prefer the odor source of lima bean infested with spider mites above that of lima bean infested with beet armyworm (Spodoptera exigua).…”
Section: Introductionmentioning
confidence: 99%
“…Spider mite-infested tomato plants emit signiWcantly more TMTT than uninfested tomato plants . The role of TMTT in the attraction of predatory mites has been investigated with lima bean (Phaseolus lunatus) as model system (De Boer et al 2004). Predatory mites prefer the odor source of lima bean infested with spider mites above that of lima bean infested with beet armyworm (Spodoptera exigua).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to dissect the volatile signal emitted by herbivore-damaged leaves of lima bean (1) and maize (8), for instance, could not identify a specific compound responsible for enemy attraction, suggesting that mixtures constitute the active signal. However, the application of individual plant volatiles, such as methyl salicylate and the sesquiterpene alcohol nerolidol, in behavioral assays have been occasionally reported to attract parasitoids (9) and predatory mites (10)(11)(12).…”
mentioning
confidence: 99%
“…Notably, (E)-DMNT and TMTT have also been reported to function as airborne cues that attract predatory mites (de Boer et al 2004;Kappers et al 2005), which may explain our previously reported findings that infested, second receiver plants that had been placed near infested VOCos-receiver plants were more attractive to P. persimilis in comparison to those that had been placed near the infested VOCwt-receiver plants (Muroi et al 2011). …”
mentioning
confidence: 68%